Nebulized Heparin Attenuates Pulmonary Coagulopathy and Inflammation through Alveolar Macrophages in a Rat Model of Acute Lung Injury - Chimenti, Laura; Camprubí-Rimblas, Marta; Guillamat-Prats, Raquel; Gomez, Maria Nieves; Tijero, Jessica; Blanch, Lluis; Artigas, Antonio (Thrombosis and Haemostasis, 2017)
Objective Alveolar macrophages play a key role in the development and resolution of acute respiratory distress syndrome (ARDS), modulating the inflammatory response and the coagulation cascade in lungs. Anti-coagulants may be helpful in the treatment of ARDS. This study investigated the effects of nebulized heparin on the role of alveolar macrophages in limiting lung coagulation and inflammatory response in an animal model of acute lung injury (ALI).Methods Rats were randomized to four experimental groups. In three groups, ALI was induced by intratracheal instillation of lipopolysaccharide (LPS) and heparin was nebulized at constant oxygen flow: the LPS/Hep group received nebulized heparin 4 and 8 hours after injury; the Hep/LPS/Hep group received nebulized heparin 30 minutes before and 4 and 8 hours after LPS-induced injury; the LPS/Sal group received nebulized saline 4 and 8 hours after injury. The control group received only saline. Animals were exsanguinated 24 hours after LPS instillation. Lung tissue, bronchoalveolar lavage fluid (BALF) and alveolar macrophages isolated from BALF were analysed.Results LPS increased protein concentration, oedema and neutrophils in BALF as well as procoagulant and proinflammatory mediators in lung tissue and alveolar macrophages. In lung tissue, nebulized heparin attenuated ALI through decreasing procoagulant (tissue factor, thrombin–anti-thrombin complexes, fibrin degradation products) and proinflammatory (interleukin 6, tumour necrosis factor alpha) pathways. In alveolar macrophages, nebulized heparin reduced expression of procoagulant genes and the effectors of transforming growth factor beta (Smad 2, Smad 3) and nuclear factor kappa B (p-selectin, CCL-2). Pre-treatment resulted in more pronounced attenuation.Conclusion Nebulized heparin reduced pulmonary coagulopathy and inflammation without producing systemic bleeding, partly by modulating alveolar macrophages.
Keywords: acute respiratory distress syndrome; acute lung injury; anti-coagulants; heparin; alveolar macrophages